PENGARUH MODEL PEMBELAJARAN CONTROVERSIAL ISSUES TERHADAP KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK KELAS X PADA MATA PELAJARAN EKONOMI DI MAN MODEL SEKAYU - Izza Aprilianti Wardani; M. Djahir Basir; Ikbal Barlian (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2017)
This study discuss about the influence instructional model of controversial issues toward student ten grade’s critical thinking skills of Economic subject in MAN Model Sekayu. Formulation problem of this study is whether there is differentiation influence between instructional model of controversial issues and problem based instruction toward ten grades student’s critical thinking skills or not. This is an experimental research using quasi experimental non equivalent control group design with pretest post-test form. The population were all of social ten grade students of MAN Model Sekayu. Sampling technique was cluster random sampling thus X social 2 was chosen as experimental group and X social 3 as control group. The data were got through test and observation. The result of experimental group’s observation interpreted into critical thinking skills was critic. T-test was used to test the hypothesis. The calculation gained t calculate > t tabe, so that Ho was rejected and Ha was accepted. Thus, there was differentiation influence between instructional model of controversial issues and problem based instruction toward ten grade student’s critical thinking skills of Economic subject in MAN Model Sekayu. There were some difficulty when students explained, argued and discussed their argument about controversial issues discussed, such as the condition of class that couldn’t be controlled, lack of self confidence, and giving the conclusion was not based on the advantages and weaknesses of the argument.